2008
DOI: 10.1007/s11104-008-9841-8
|View full text |Cite
|
Sign up to set email alerts
|

Grain yield, above-ground and root biomass of Al-tolerant and Al-sensitive wheat cultivars under different soil aluminum concentrations at field conditions

Abstract: Considering the importance of acidic conditions and Al toxicity in arable soils of Chile, 2 field experiments were conducted in the 2005-06 and 2006-07 growing seasons in Valdivia (39°47′18′′S, 73°14′05′′W), Chile in an Andisol. The objective of this experiment was to quantitatively evaluate the effect of different soil exchangeable Al levels on grain yield, and above-ground and root biomass of Altolerant and Al-sensitive wheat cultivars under field conditions. Treatments were a factorial arrangement of: i) tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…Similarly, [9] reported a decrease in bean yield in response to increasing Al saturation. In agreement with the results of this study, [32] reported that toxic levels of aluminium (Al) in acid soils inhibited root growth and caused substantial reductions in yields of Al-sensitive crops. The higher vegetative biomass yield of new BILFA 58 than Roba 1 could be attributed to its greater tolerance to soil acidity.…”
Section: Disscusionsupporting
confidence: 91%
“…Similarly, [9] reported a decrease in bean yield in response to increasing Al saturation. In agreement with the results of this study, [32] reported that toxic levels of aluminium (Al) in acid soils inhibited root growth and caused substantial reductions in yields of Al-sensitive crops. The higher vegetative biomass yield of new BILFA 58 than Roba 1 could be attributed to its greater tolerance to soil acidity.…”
Section: Disscusionsupporting
confidence: 91%
“…In agreement with the results of this study, Kushwaha et al (2017) reported a decrease in pod weight and pod yield in response to aluminium treatment in soil. Corroborating with the present result, Valle et al (2009) reported that toxic levels of aluminium (Al) in acid soils inhibited root growth and caused substantial reductions in yields of Al-sensitive crops.…”
Section: Genotypessupporting
confidence: 89%
“…Considering the spatial characteristics for the soil hydraulic properties of the studied Andisols (Figure 1, 2, 3), the irrigation scheduling can be crucial for the water availability for roots. Furthermore, the ability of plant roots to penetrate the soil profile is limited by physical and chemical properties, such as the soil Bd (Figure 1 a) and the presence of Al, respectively (Valle et al, 2009). …”
Section: The Spatial Variability Of Soil Hydraulic Parametersmentioning
confidence: 99%